Investigating mental health disparities in rural sexual and gender minority adults: protocol for the rural exploration and approaches to LGBTQ + Mental Health (REALM) prospective cohort study - Shoshanna L. Fine; Kalai Willis; Iaah L. Lucas; Kirsten F. Siebach; Jennifer L. Glick; Mariah Valentine-Graves; Savannah Winter; Michael Smith; Thomas Waltz; Gina Bailey Herring; Marissa Hannah; Holly C. Wilcox; et al. (BMC Public Health)
Abstract Background Sexual and gender minority (SGM) persons experience substantial mental health disparities throughout the life course, including increased vulnerability to depression and suicide. Few existing studies, however, have explored how pervasive experiences of SGM-related stigma, discrimination, and trauma (i.e., minority stress) contribute to adverse mental health outcomes among diverse sub-populations of SGM adults living in rural areas of the United States. This paper describes the protocol for a prospective cohort study, “Rural Exploration and Approaches for LGBTQ + Mental Health (REALM),” that will explore minority stress in relation to mental health conditions and suicidal behaviors among rural SGM adults. Methods Online processes will be used to recruit and enroll a diverse sample of up to 2,500 SGM adults aged 18 + living in rural counties and small metropolitan areas in the United States to complete an online baseline survey. This will include: up to 1,000 cisgender sexual minority persons (up to n = 500 each cisgender women and cisgender men); and up to 1,500 gender minority persons (up to n = 500 persons who were assigned male at birth and identify as a woman, female, and/or transfeminine; up to n = 500 persons who were assigned female at birth and identify as a man, male, and/or transmasculine; and up to n = 500 persons who identify as some other gender, including non-binary, gender non-conforming, and/or agender regardless of sex assigned at birth). All enrolled participants will subsequently be followed over a 12-month period, with repeated surveys at three-month intervals. Included survey measures will focus on sociodemographic information, mental health, substance use, suicidal behaviors, minority stressors, psychological processes, and other related risk and protective factors. Discussion This study presents a critical opportunity to better understand how minority stress contributes to adverse mental health outcomes among populations that remain underrepresented in research and programs in 2024. Results will be used to create more targeted, acceptable, and impactful intervention content and strategies that mitigate stigma, promote mental health, and prevent suicidal behaviors among rural SGM adults.